Optimization Techniques of Decision Making - Decision Tree - TOFAN, Cezarina Adina (Advances in Social Sciences Research Journal, 2014)
Modern methods of modeling and simulation of manufacturing processes inevitably lead to a tendency to standardize management judgment to perception phenomena specific industrial management and performance of decision-making. Considering that what happens in a production system similar repeated in other similar systems, identifying an acceptable method of solving problems categories, adopting the same decision in similar situations is convenient and prompt. However, every problem has a unique character management undisputed that a number of specific elements have content, performance or behaviors different single generalized model, the manager must identify those features that lead to the conclusion that every problem, at least partially, is a special case, singular. The realities of the modern society shows us that with the development of the market economy and its increasing complexity, the economic information has to develop appropriately, because it can provide the necessary elements to make decisions, to be able to reflect exactly the patrimonial situation of the economic operators and the economic and financial results, the main objective is to increase the firm value. Management through functions and its attributes is what determines the business objectives, the necessary resources to achieve them and the distribution of the results created by using of these resources. The raw materials that constitute the basis of the management are information and people